The EFFECT OF BEVACIZUMAB ON α-SMOOTH MUSCLE ACTIN EXPRESSION AND FIBROBLAST COUNT IN TRABECULECTOMY AREA TOWARDS PREVENTION OF FIBROSIS - Sekar Ayu Sitoresmi Sekar Ayu (Stem Cell Research and Development Center, Universitas Airlangga, 2022)
Objective to analyze the effect of bevacizumab on α-smooth muscle actin expression and fibroblast count in trabeculectomy area of rabbit models in order to find a safer modulator of wound healing to improve surgical outcome. Material and methods 16 New Zealand white rabbits aged 4-6 months and weigh between 2,5-3,5 kg were performed trabeculectomy in their right eyes with postoperative subconjunctival injection of BSS and Bevacizumab. Rabbits were put into control and bevacizumab group using simple random sampling. Examination were done postoperative day 1, 7, and 14 and subjects were terminated and performed enucleation on postoperative day 14. The samples were histologically stained with Haematoxyline-Eosin to count the fibroblast and immunohistochemistry using α-smooth muscle actin antibody to differ the myofibroblast from fibroblast and the expression of α-SMA were collected using immunoreactive score. Result Mann Whitney u test and independent t-test were used to analyze the data, and we found both less expression of α-smooth muscle actin and fibroblast count on bevacizumab group compared to control group which indicates less myofibroblast, fibroblast, and less scarring potential in trabeculectomy area. Conclusion bevacizumab inhibits fibroblast proliferation and its differentiation to myofibroblast that lead to less collagen production and fibrosis.